Seroprevalence and pathology of Mycoplasma gallisepticum infection in layer birds (Asian Journal of Medical and Biological Research, 2024)
Avian mycoplasmosis, caused by Mycoplasma gallisepticum (MG), imposes a significant threat to the poultry industry in Bangladesh, leading to considerable economic losses. This study aimed to determine the seroprevalence of MG and characterize the associated pathology in MG-infected layer birds from different geographical areas within the Nilphamari district. Our hypothesis suggested that the seroprevalence of MG infection in layer birds may vary based on geographical location within the Nilphamari district of Bangladesh, with higher prevalence expected in areas with colder temperatures, such as during the winter season, and in densely populated poultry farming regions. For the serum plate agglutination test, 400 random blood samples were collected, while tissue samples from suspected layer birds with respiratory distress were obtained from 40 commercial layer farms for histopathological analysis. The serum plate agglutination test revealed an overall seroprevalence of MG of 64.25%, with the highest prevalence occurring during the winter season (70%), particularly among layer birds aged 20-40 weeks. Moreover, the seroprevalence of MG was significantly higher in Kishoregonj upazila (68%) compared to Nilphamari sadar (62%). Gross examination of MG-infected layer birds unveiled characteristic features such as tracheal hemorrhages and mucous accumulation, pulmonary edema and hemorrhages, and air sac cloudiness. Histopathological observations included tracheal mucosal sloughing and increased goblet cell numbers, as well as lung edema, hemorrhages, and tissue destruction, alongside significant reactive cell infiltration and exudation in the air sacs. By shedding light on the current MG infection status in layer chickens within the Nilphamari district, this study provides valuable insights to aid poultry industry stakeholders in formulating preventive strategies and enhancing the overall health and welfare of poultry flocks.Asian J. Med. Biol. Res. 2024, 10(1), 58-66